ANALYSIS OF LOCAL GOVERNMENT FINANCIAL PERFORMANCE IN REGENCIES/CITIES IN EAST NUSA TENGGARA PROVINCE - Ratnadilla Ukkas; Thomas Ola Langoday; Simon Sia Niha (Jurnal Ekonomi, 2023)
The aim of this research is to determine the significance of the influence of Economic Growth, Labor, Capital Expenditures and Employee Expenditures on the Financial Performance of Regency and City Governments in NTT. This research approach uses quantitative methods. The sample used in this research is data from districts and cities in East Nusa Tenggara Province, totaling 21 districts and 1 city. Data was collected using documentation techniques and analyzed using Eviews. Observations in this research used Panel Data from 2017-2021. The results of the research show that simultaneously Economic Growth, Labor, Capital Expenditures and Personnel Expenditures have a significant effect on Regional Financial Performance, while partially Economic Growth and Labor have a positive and insignificant effect on Regional Financial Performance, Personnel Expenditures and Capital Expenditures have a positive influence and significant to Regional Government Financial Performance. The R square value shows that the contribution of Economic Growth, Labor, Capital Expenditures and Employee Expenditures is 95.63%, while the rest is influenced by other variables which were not examined in this research.